Application of the Right to Permanent Sovereignty over Natural Resources for Indigenous Peoples: Assessment of Current Legal Developments. - Enyew, Endalew Lijalem (Arctic Review on Law and Politics, 2017)
Source at https://doi.org/10.23865/arctic.v8.947 The right to Permanent Sovereignty over Natural Resources (PSNR) emerged in the era of decolonization. As a reaction to the irresponsible exploitation of natural resources by colonial powers, peoples under colonial rule and newly independent developing states asserted the right to control and dispose of their own natural resources. The UN General Assembly recognized and reinforced these claims by adopting a series of resolutions relating to the right to PSNR so as to facilitate the process of decolonization. However, the subjects of the right to PSNR have expanded to include ‘all peoples’ due to legal developments in international law pertaining to the right to self-determination of peoples and other human rights standards. This article explores the contemporary application of the right to PSNR for indigenous peoples, by virtue of their being ‘peoples’, tracing various developments in international law relating to indigenous peoples since the inception of PSNR in the 1950s.